PECULIARITIES OF INTEGRATED MASTER OF PHARMACY DEGREE PROGRAMS (MPHarm) IN THE UNIVERSITIES OF GREAT BRITAIN (Comparative Professional Pedagogy, 2023)
The article studies the peculiarities of integrated Master of Pharmacy degree programmes (MPharm) in the universities of Great Britain.It is established that pharmacy education in the UK provides students with knowledge and skills they need to succeed in all potential career paths for pharmacists – community pharmacy, hospital pharmacy, industry, research or postgraduate study. The need to take into account anticipatory and proportional approaches to designing the content of pharmaceutical education and use effective learning techniques adapted to changes in professional activity is emphasized. The MPharm program encompasses basic and applied science, clinical and professional practice in the context of patient care. It covers three main branches of training (biological science and therapeutics, pharmaceutical science and professional practice), which are provided by year-long modules and implemented into practice through interaction with real patients. Significant differences between qualification descriptors for Bachelor with Honors (HE3) and Master (HE4) degrees under the UK Higher Education Qualifications Framework are characterized. The peculiarities of the integrated Master of Pharmacy degree programs (Mpharm) are outlined. They include the complexity of the program; practice-oriented approach; integration of theory and practice; introduction to professional activities (the opportunity to practise in a pharmacy or other pharmaceutical institutions, where students get experience working with patients and observing pharmacists’ work); preparation for registration and obtaining a pharmaceutical license. It is found that in MPharm programs, the traditional emphasis on the scientific training has been shifted to the encouragement of pharmacy practice and clinical pharmacy. In this regard, there was a shift in the educational training of pharmacists from pure sciences (chemistry, biology, physiology) to new subject areas, which include biotechnology, pharmacoeconomics, pharmacovigilance, critical evaluation, and management skills.It is defined that some pharmaceutical schools have improved their undergraduate programs by incorporating self-directed learning, expanding individual student opportunities, and implementing a lifelong learning strategy into pharmacists’ training.
Keywords: Master of Pharmacy degree program (Mpharm); Great Britain; pharmacist; pharmacy schools; professional training; qualification descriptors; educational programs; clinical pharmacy